PENGARUH PROSES REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PADA SETULUS KOFFEE - Suparwi, Suparwi; Indra Syahputra, Ari (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2023)
Abstract : The purpose of this study is to know the hiring and selection plans of employees on the quarter of the race, and the preening of the recruiting and selection process against the actual performance of an employee of the Setulus koffee. This method of research employs the process of triangulation techniques of observation, interview, and documentation. The population of this study was 43 applicants and employees at Setulus koffee, and two samples were selected of the new ones who took the positions of cashier and the old barista. Many times the manager of Setulus koffee tried to hire an employee but the result was always unsatisfactory, while the human resource facility was the most important thing for a manager at Setulus koffee to run the coffee shop operational. A problem that often arises is the unprofessional of employees sensations, such as not following the standard oprational procedure, retiring to a time of transition, deviousness, etc. Researchers are trying to do research on a new recruiting process on sehonesthearted at Setulus koffee to observe the actual event. In the process of recruiting and new selection on June 29, 2022 The researchers found that the methods employed by the recruiter improved by more attitude and attitude than the work experience of recruiting new staff potential, according to the experience of the previous recruiter that the candidate who is too professional and has too much experience tends to be difficult to control and not follow the SOP on as well as Setulus koffee. Based on those experiences can result in better employee performance.